Clusters of test anxiety in lower secondary students: a cross-cultural comparison between France and Switzerland - Valls, Marjorie; Sessa, Gwenaelle; Tardif, Eric; Mascret, Nicolas (Frontiers in Education, 2025)
IntroductionThis study investigates test anxiety among French and Swiss students. By combining variable-centered and person-centered approaches, it examines cross-cultural and gender differences to identify student profiles and guide tailored educational strategies.MethodsA sample of 538 students (269 girls; Mage = 13.43 years old) completed the French Revised Test Anxiety + Regulatory scale. Multi-group confirmatory factor analyses were used to establish measurement invariance. Variable-centered analyses (t-tests, ANOVAs) and person-centered cluster analyses were conducted to assess differences by country and gender.ResultsMeasurement invariance across countries was confirmed. French and Swiss students showed similar overall anxiety levels, but Swiss students reported higher bodily symptoms. Gender differences were pronounced, with girls reporting higher levels of worry, tension, and bodily symptoms, and boys scoring higher in perceived control. Cluster analysis identified four profiles: Tense, Low-test-anxious, Mind-wandering, and High-test-anxious students. French students were more likely to fall into the “Tense” group, while Swiss students were overrepresented in the “High-test-anxious” cluster. Gender significantly influenced cluster membership, with girls more likely to be high in anxiety and low in control.DiscussionEducational context might influence the experience of test anxiety beyond cultural similarity. Early academic selection in Switzerland may increase stress responses. Integrating perceived control into the model of test anxiety enhances understanding of student profiles and supports the development of targeted educational interventions to improve emotional regulation and academic success.